Cognitive impairments and mental health of patients with post-COVID-19: A cross-sectional study - Morawa, Eva; Krehbiel, Johannes; Borho, Andrea; Herold, Regina; Lieb, Marietta; Schug, Caterina; Erim, Yesim (Journal of Psychosomatic Research, 2023)
Background: Persistent cognitive complaints belong to the most frequent symptoms after COVID-19. This study explored the neuropsychological profile, mental health and risk factors for cognitive impairment in post-COVID-19 patients. Methods: The patients were recruited consecutively in the Post COVID Center of the University Hospital of Erlangen between 12/2022 and 05/2023. They underwent an extensive neuropsychological assessment including the Verbal Learning Memory Test (VLMT), the digit span backwards from the Wechsler Memory Scale-Revised (WMS-R), the Trail Making Test (TMT) Part A and B, the d2 Test of Attention and the Regensburger Verbal Fluency Test (RWT). For each cognitive domain we calculated the frequency of age-adjusted scores below the measure-specific norms. Depressive symptoms were measured with the Patient-Health-Questionnaire-9 (PHQ-9). Logistic regression analyses were computed. Results: In 110 patients (mean age: 42.5 ± 11.9 years; 68.2% women), the most frequent cognitive deficits were observed for verbal fluency, working speed, delayed recall and attention. In almost every cognitive domain high education levels were associated with a decreased risk for cognitive impairment. Higher age was a risk factor for working speed and delayed recall and a protective factor for verbal fluency. Clinically relevant depressive symptoms were associated with an elevated risk for an impairment regarding some cognitive functions. Conclusion: Cognitive dysfunctions were common among the post-COVID-19 patients. Differentiated exploration of cognitive impairments is crucial for a proper characterization of the post-COVID syndrome. In future research parameters of cognitive impairment should be correlated to alterations in biological markers of the disease like markers of immunological and microcirculation change.
CRIS-Team Scopus Importer:2023-08-18
Keywords: Cognitive deficits; Cognitive impairment; COVID-19; Depression; Mental health; Neurocognitive function; Post-COVID-19